2017
DOI: 10.1002/2327-6924.12505
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an evidence-based clinical decision support tool to improve the detection, evaluation, and referral patterns of adult chronic kidney disease patients in primary care

Abstract: Background and purpose Chronic kidney disease (CKD) is undertreated and under‐recognized in primary care. The majority of primary care providers (PCPs) are not aware or knowledgeable of current CKD guidelines. The purpose of this project was to develop a quality improvement intervention for PCPs through the delivery of evidence‐based guidelines at the point of care. Methods An evidence‐based clinical algorithm was developed in the electronic medical record for providers to access within one organization compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…The study selection process (Figure 2) identified 60 studies 3190 for inclusion, including 56 original articles 3136,3851,5355,5763,6590 and four abstracts. 37,52,56,...…”
Section: Resultsmentioning
confidence: 99%
“…The study selection process (Figure 2) identified 60 studies 3190 for inclusion, including 56 original articles 3136,3851,5355,5763,6590 and four abstracts. 37,52,56,...…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, the Evidence Based Practice Project implemented a clinical decision tool for CKD into the electronic medical record system of primary care physicians, physician assistants, and nurse practitioners. 21 One of the goals of this program is to educate providers on the risk factors, staging, management, and outcomes of their patients with CKD in order to improve early detection rates and long term management. 21 As a result of this project, more patients were correctly diagnosed with CKD, detection rates improved, and appropriate referrals to nephrologists increased.…”
Section: Discussionmentioning
confidence: 99%
“…21 One of the goals of this program is to educate providers on the risk factors, staging, management, and outcomes of their patients with CKD in order to improve early detection rates and long term management. 21 As a result of this project, more patients were correctly diagnosed with CKD, detection rates improved, and appropriate referrals to nephrologists increased. This showed that evidence-based medicine is a valuable tool for primary care providers, especially when implemented into electronic medical record systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demiris et al constructed a pulse recognition model using BP networks to improve the efficiency and accuracy of pulse diagnosis [ 16 ]. Regan constructed a pulse classification model by combining convolutional neural networks and recursive graphs, which further improved the efficiency and accuracy of pulse diagnosis [ 17 ]. Loftus et al constructed a tongue classifier using vectorized neural networks and achieved very promising results [ 18 ].…”
Section: Related Workmentioning
confidence: 99%